2012
DOI: 10.1161/circep.111.969519
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Frequency Gradients During Persistent Atrial Fibrillation in Sheep Are Associated With Stable Sources in the Left Atrium

Abstract: Background Dominant frequencies (DFs) of activation are higher in the atria of patients with persistent than paroxysmal atrial fibrillation (AF) and left-to-right atrial (LA-to-RA) DF gradients have been identified in both. However, whether such gradients are maintained as long-term persistent AF is established remains unexplored. We aimed at determining in-vivo the time-course in atrial DF values from paroxysmal to persistent AF in sheep, and test the hypothesis that a LA-to-RA DF difference is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 30 publications
6
56
1
Order By: Relevance
“…Electrograms at FIRM-identified ablation sites were not found to differ in dominant frequency or Shannon entropy values compared with the atrial regions that did not harbor focal AF drivers. Conversely, in both animal models 10,[27][28][29] and other human studies, rotor sites have demonstrated a higher frequency 11,12 than other atrial regions. Intuitively, if a rotor is to be a driver of fibrillation it would be expected to have a higher frequency than surrounding atrial myocardium, [30][31][32] with a negative activation frequency gradient away from the high-frequency source as part of fibrillatory conduction.…”
Section: Circ Arrhythm Electrophysiolmentioning
confidence: 87%
“…Electrograms at FIRM-identified ablation sites were not found to differ in dominant frequency or Shannon entropy values compared with the atrial regions that did not harbor focal AF drivers. Conversely, in both animal models 10,[27][28][29] and other human studies, rotor sites have demonstrated a higher frequency 11,12 than other atrial regions. Intuitively, if a rotor is to be a driver of fibrillation it would be expected to have a higher frequency than surrounding atrial myocardium, [30][31][32] with a negative activation frequency gradient away from the high-frequency source as part of fibrillatory conduction.…”
Section: Circ Arrhythm Electrophysiolmentioning
confidence: 87%
“…A critical obstacle for the elucidation of mechanisms responsible for chronic AF lies in the practical challenges associated with the development of experimental models that reproduce the electrophysiological characteristics of atrial remodeling. Animal models involve subjecting animals to weeks or months of sustained atrial arrhythmias, which implies significant economical, ethical, and time burdens (11,20). Other experimental models include in vitro cell cultures, which are typically obtained from neonatal rat hearts.…”
Section: Discussionmentioning
confidence: 99%
“…22 To establish the patterns of activation underlying the DF max values in the LA we used phase movies 13 to correlate those with reentries in the PLA and LAA. 23 In Figure 3A a dynamic combination of breakthroughs (BTs) and reentries is seen in the PLA and LAA during AF, with a rotor drifting from the PLA towards the LAA (See Video).…”
Section: Introductionmentioning
confidence: 99%